Extracellular ATP/adenosine dynamics in the brain and its role in health and disease - Shigetomi, Eiji; Sakai, Kent; Koizumi, Schuichi (Frontiers in Cell and Developmental Biology, 2024)
Extracellular ATP and adenosine are neuromodulators that regulate numerous neuronal functions in the brain. Neuronal activity and brain insults such as ischemic and traumatic injury upregulate these neuromodulators, which exert their effects by activating purinergic receptors. In addition, extracellular ATP/adenosine signaling plays a pivotal role in the pathogenesis of neurological diseases. Virtually every cell type in the brain contributes to the elevation of ATP/adenosine, and various mechanisms underlying this increase have been proposed. Extracellular adenosine is thought to be mainly produced via the degradation of extracellular ATP. However, adenosine is also released from neurons and glia in the brain. Therefore, the regulation of extracellular ATP/adenosine in physiological and pathophysiological conditions is likely far more complex than previously thought. To elucidate the complex mechanisms that regulate extracellular ATP/adenosine levels, accurate methods of assessing their spatiotemporal dynamics are needed. Several novel techniques for acquiring spatiotemporal information on extracellular ATP/adenosine, including fluorescent sensors, have been developed and have started to reveal the mechanisms underlying the release, uptake and degradation of ATP/adenosine. Here, we review methods for analyzing extracellular ATP/adenosine dynamics as well as the current state of knowledge on the spatiotemporal dynamics of ATP/adenosine in the brain. We focus on the mechanisms used by neurons and glia to cooperatively produce the activity-dependent increase in ATP/adenosine and its physiological and pathophysiological significance in the brain.